Peripheral hemodynamics and microcirculation dynamics in arterial hypertension patients receiving bisoprolol monotherapy - M. V. Lozhakova (Кардиоваскулярная терапия и профилактика)
Aim. To study eight-week bisoprolol therapy effects on peripheral hemodynamics and microcirculation (MC) parameters.Material and methods. The study included 34 patients with stage II arterial hypertension (AH): 18 men, 16 women; median age 47 years. At baseline and after 8 weeks of bisoprolol therapy (10 mg once a day), all participants underwent 24-hour blood pressure monitoring (BPM), peripheral hemodynamics and MC assessment.Results. Eight-week bisoprolol therapy (10 mg/d) was associated with target BP level achievement in 74% of the patients. In 76%, circadian BP profile had been normalized. Bisoprolol treatment also improved peripheral hemodynamics and MC parameters. Significant reduction in total peripheral vascular resistance and pulse wave velocity was observed in 95%, normalization of these parameters - in 54%. MC parameters normalized in 67% and improved in 94%.Conclusion. Bisoprolol demonstrated high antihypertensive activity and beneficial effects on peripheral hemodynamics and MC parameters.